1999
DOI: 10.1063/1.370192
|View full text |Cite
|
Sign up to set email alerts
|

Laser-stimulated luminescence of yttria-stabilized cubic zirconia crystals

Abstract: The kinetics of laser-stimulated luminescence (LSL) of yttria-stabilized cubic zirconia single crystals is investigated. Excitation of ZrO2⋅9.5%Y2O3(100) and (110) using ns pulses of 213 nm (5.82 eV), 266 nm (4.66 eV), and 355 nm (3.49 eV) photons produce LSL bands with Gaussian profiles and peak maxima at 460 nm (2.69 eV), 550 nm (2.25 eV), and 600 nm (2.07 eV), respectively. LSL involves a single-photon process for energy densities below ∼1.0 MW/cm2. Decay times vary from 0.1 to 100 μs depending on the excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
109
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 51 publications
11
109
2
6
Order By: Relevance
“…Broad unstructured deep level recombination in the yellow/orange spectral region has been observed in the different ZrO 2 polymorphs and assigned to F-type defects, involving the oxygen vacancy and their complexes. [35][36][37][38] Overlapped with the F-type emission band, the as-grown cubic stabilized ZrO 2 fibers show an additional emission in the red region with pronounced maxima at 614 nm ͑2.02 eV͒ and 641 nm ͑1.93 eV͒. These maxima were previously observed in polycrystalline YSZ and were attributed to the intraionic recombination of a lanthanide ion present as a contaminant in the samples.…”
Section: Resultssupporting
confidence: 51%
“…Broad unstructured deep level recombination in the yellow/orange spectral region has been observed in the different ZrO 2 polymorphs and assigned to F-type defects, involving the oxygen vacancy and their complexes. [35][36][37][38] Overlapped with the F-type emission band, the as-grown cubic stabilized ZrO 2 fibers show an additional emission in the red region with pronounced maxima at 614 nm ͑2.02 eV͒ and 641 nm ͑1.93 eV͒. These maxima were previously observed in polycrystalline YSZ and were attributed to the intraionic recombination of a lanthanide ion present as a contaminant in the samples.…”
Section: Resultssupporting
confidence: 51%
“…The broadband emission centered at 4.4 eV observed in high-quality crystalline material has been ascribed to self-trapped excitons [6], whereas the origin of lowerenergy bands is still unclear although the various intrinsic or extrinsic defects (especially oxygen vacancies) are the most probable cause [12]. This is also supported by the observation that the UV-excited emission of nanocrystalline zirconia is sensitive to the oxygen content in the ambient [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…Nevertheless, the rise of intensity of the peak at 2.22 eV in the present study has another possibility against the previous assignment [2]; the peak at 2.53 eV for the unperturbed vacancy (F-type) and the peak at 2.22 eV for the perturbed vacancy (F A -type). The previous assignment was based on a report for the undoped zirconia which claimed 2.69 eV as PL peak energy for vacancy state [5], and suggested that the same type of vacancy also has a PL peak at around 2.5 eV [6]. However, we still prefer our choice above when we take the results for Sc-and In-8YSZ [3] into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…3. Judging from the fact that undoped zirconia yields the peak of 2.69 eV and the addition of scandium or indium oxide both results in emergence of the peak at 2.70 eV, the doping of Sc 3+ , and probably In 3+ also, may induce photo-excitation to the conduction band, because the peak at 2.69 eV is for the recombination of photo-excited carrier at conduction band with hole in unperturbed oxygen vacancy state [5]. The temperature dependence observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation